Determination of structural performance of 3D steel pipe rack suspended scaffolding systems - Arslan, Guray; Sevim, Baris; Bekiroglu, Serkan (TECHNO-PRESS, 2017)
This study investigates the structural performance of 3D steel pipe rack suspended scaffolding systems. For the purpose, a standard full scale 3D steel pipe rack suspended scaffolding system considering two frames, two plane trusses, purlins and wooden floor is constructed in the laboratory. A developed load transmission system was placed in these experimental systems to distribute single loads to the center of a specific area in a step-by-step manner using a load jack. After each load increment, the displacements are measured by means of linear variable differential transducers placed in several critical points of the system. The tests are repeated for five different system conditions to determine the structural performance. The means of system conditions is the numbers of the tie bars which are used to connect plane trusses under level. Finite elements models of the 3D steel pipe rack suspended scaffolding systems considering different systems conditions are constituted using SAP2000 software to support the experimental tests and to use the models in future studies. Each of models including load transmission platform is analyzed under a single loading and the displacements are obtained. In addition, to calibrate the numerical models some uncertain parameters such as elasticity modulus of wooden floor and connection rigidity of purlins to plane trusses are assessed experimentally. The results of this work demonstrate that when increasing numbers of tie bars the displacement values are decreased. Also the results obtained from developed numerical models have harmony with those of experimental. In addition, the scaffolding system with two tie bars at the beginning and at the end of the plane truss has the optimum structural performance compared the results obtained for other scaffolding system conditions.
Keywords: 3D steel pipe rack suspended scaffolding system; developed load transmission platform; experimental test; finite element model; laboratory model; structural performance; tie bar; FRAME STRUCTURES; BEAMS; ENGINEERS; DESIGN; COST; Engineering